Ornithomorphic image of an eagle in the shamanic tradition of the peoples of Siberia (Sakha, Khakas, Tuva) - Toktorbayeva, A.B.; Sharip, A.Zh. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
The article comprehensively examines ornithomorphic images in the shamanic traditions of the peoples of Siberia. Ornithomorphic symbols occupy a special place in the shamanic worldview because they have an important function in establishing contact with the spirit world, in depicting cosmogonic concepts. The article analyzes the symbolic meaning of the images of birds in the shamanic rituals of these peoples, including the Eagle. The relevance of the study is due to a deeper understanding of the cultural heritage of the peoples of Siberia (Sakha, Khakas, Tuva), including the ritual, symbolic, and worldview significance of the ornithomorphic image of the Eagle in shamanic traditions. The study of ornithomorphic images allows us to consider the spiritual world and mythological concepts of the Sakha, Khakas, and Tuva peoples from a new angle. The article analyzes the symbolic meaning of the images of the Eagle in shamanic rituals and the attributes of these peoples. Mythological, ethnographic, and culturological methods were used in the study. In mythological analysis, the meaning of the image of the Eagle in the shamanic worldview is revealed, and their role is determined. Ethnographic methods made it possible to study the role of the Eagle in shamanic practices. Archaeological materials served as the basis for the study of shamanic attributes, the ritual function of birds from ancient times to the present day. Cultural analysis revealed not only the ritual, but also the socio-cultural significance of birds. The results of the study revealed the multifaceted role of birds in the shamanic traditions of the peoples of Siberia (Sakha, Khakas, Tuva). Eagle feathers are often found in shamanic clothing, and their images are often found in avenga (tambourine) and headdresses. Sound imitations, such as the voice of an eagle, are an important part of ritual songs and rituals. Shamanic traditions of the peoples of Siberia, based on images of birds, do not lose their relevance as a source of spiritual and cultural wealth for modern society.